Gender Difference of Attitude and Willingness towards Kidney Donation and Sale among Chinese Medical Students. (August 2017) - Ge, Fangmin; Kaczmarczyk, Gabriele; Biller-Andorno, Nikola
Abstract : Objectives: Since kidney is the primary organ in need for transplantation, it is of significance in unveiling gender difference of willingness and attitudes towards kidney donation and sale among Chinese medical students in a hypothetical regulated kidney market. Methods: This quantitative research was studied among Chinese female and male medical students by using a 34-item piloted questionnaire. The data was analyzed by GraphPad Prism Software. Results: 320 participants at a median age of 24 years were surveyed. Twenty percent of the surveyed medical students would consider selling a kidney in a regulated kidney market. Among them, 68.2% would sell only to overcome a particularly difficult financial situation. Only 37 out of 107 (34.6%) endorsing a regulated market would be willing to sell a kidney. Gender difference had a marginal association with willingness to sell a kidney (p=0.0831), whereas the religiosity and socio-economic status of respondents were significantly related with willingness to donate a living- or posthumous kidney (see fig. 1). FIGURE 1. The rate of willingness of religious or non-religious respondents toward acceptance of kidney transplantation, living donation to a loved one and living donation in a regulated market Figure. No caption available. Figure. No caption available. Conclusions: Our results preliminarily indicated the willingness and attitude of Chinese medical students toward organ sale in such a hypothetical regulated kidney market. Attitudes toward legalizing a regulated kidney market and willingness to sell a kidney are not consistent. Gender imbalance, religiosity and socio-economic status may exert different impacts on the decision-making process for organ disposition. Keywords: gender difference, attitude, kidney sale, donation, Chinese students